2001
DOI: 10.1002/app.10015
|View full text |Cite
|
Sign up to set email alerts
|

Elongation flow studies of DNA as a function of temperature

Abstract: ABSTRACT:The response of T4-phage DNA molecules to an elongational flow field was monitored by flow-induced birefringence as a function of temperature. The flow-induced birefringence observed in this study was localized in the pure elongational flow area with a critical strain rate, indicating that the birefringence was attributed to a coilstretch transition of DNA molecules. The slight decrease in the birefringence intensity with increases in temperature to 40°C was explained by a thermal-activation process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This could also explain why there was no further development of the degradation process in this condition. As far as concerned on this half-cut phenomenon, Sasaki et al 41 explained it within a theoretical framework known as the thermally activated barrier to scission (TABS) model. 42 According to the this model, molecular degradation in an elongational flow field proceeds in two-stage processes: molecular stretching and fracture.…”
Section: Resultsmentioning
confidence: 99%
“…This could also explain why there was no further development of the degradation process in this condition. As far as concerned on this half-cut phenomenon, Sasaki et al 41 explained it within a theoretical framework known as the thermally activated barrier to scission (TABS) model. 42 According to the this model, molecular degradation in an elongational flow field proceeds in two-stage processes: molecular stretching and fracture.…”
Section: Resultsmentioning
confidence: 99%
“…These experiments found that polymers can be stretched by weak flows [5] and broken by strong extensional flows [6]. Since there are strong correlations [7] between dragreduction efficiency and extensional viscosity in polymer solutions, a study of MMD will provide a good opportunity not only in the understanding of the basic DR mechanism but also in the turbulent structures at such a small scale in the presence of polymers.…”
mentioning
confidence: 99%
“…[22] Based on the higher molecular weight of CT-DNA and the analysis of l-DNA under turbulent flow condition, [7] it can be assumed that major mechanical degradations of the CT-DNA intensively occurred right after the injection of CT-DNA into turbulent flow just in a few second. As far as this half-cut phenomenon is concerned, Sasaki et al [23] explained that molecular degradation in an elongational flow field proceeds as a two-stage process; molecular stretching and fracture. In this process, scission of the extended conformation always occurs near the midpoint, where the stress in the molecule reaches a maximum value.…”
Section: Experimental Partmentioning
confidence: 99%
“…In this process, scission of the extended conformation always occurs near the midpoint, where the stress in the molecule reaches a maximum value. [24] Regarding the critical condition of molecular degradation, they [23] also explained that the critical strain rate ( _ " f ) for fracture is related to the contour length (L) and molecular weight (M w ) of a polymer chain in an inverse square mode as:…”
Section: Experimental Partmentioning
confidence: 99%